War on Drugs, War on Women: Visualizing Female Homicide in Mexico - Fondevila, Gustavo (Women & criminal justice, 2020)
Recent literature has established that War on Drug policies lead to differentiated consequences over the lives of certain groups within the population when analyzed by race, gender, age, and/or social status. In particular is the relationship between the War on Drugs and its effects on women. The objective of this article is to analyze the asymmetric behavior of homicidal victimization between males and females that has unfolded since the beginning of the 2006 War on Drugs declared by Mexican president Felipe Calderón Hinojosa. Our findings illustrate that, from the declaration of the War on Drugs, the Mexican female population began to experience proportionally higher levels of homicidal victimization as compared with the male population, reaching its maximum level during the period between 2007 and 2010. In this sense, the present article contributes to visualize the presence of gender-differentiated effects of homicidal victimization derived from the War on Drugs in Mexico.